2016
DOI: 10.5114/fn.2016.58914
|View full text |Cite
|
Sign up to set email alerts
|

Angiocentric glioma from a perspective of A-B-C classification of epilepsy associated tumors

Abstract: A b s t r a c t Angiocentric glioma (AG) is a newly-classified, very rare, WHO grade I central nervous system (CNS) lesion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
13
1
1
Order By: Relevance
“…According to the WHO Classi cation, 2016 edition 40 , glioma are classi ed as diffuse gliomas (astrocytoma, oligodendroglioma, glioblastoma), as well as circumscribed and low-grade gliomas (angiocentric glioma, pilocytic astrocytoma, subependymal giant cell astrocytoma, pleomorphic xanthoastrocytoma, pilomyxoid astrocytoma, ependymoma, myxopapillary ependymoma, and subependymoma). Some study results showed that most patients with angiocentric glioma were children and young people, with no signi cant gender difference, and epilepsy was the main clinical manifestation 41 . Diffuse astrocytoma and oligodendroglial tumors were common in the cerebral hemisphere of young patients (frontal and temporal lobes were common), and epilepsy was one of the most common clinical symptoms 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the WHO Classi cation, 2016 edition 40 , glioma are classi ed as diffuse gliomas (astrocytoma, oligodendroglioma, glioblastoma), as well as circumscribed and low-grade gliomas (angiocentric glioma, pilocytic astrocytoma, subependymal giant cell astrocytoma, pleomorphic xanthoastrocytoma, pilomyxoid astrocytoma, ependymoma, myxopapillary ependymoma, and subependymoma). Some study results showed that most patients with angiocentric glioma were children and young people, with no signi cant gender difference, and epilepsy was the main clinical manifestation 41 . Diffuse astrocytoma and oligodendroglial tumors were common in the cerebral hemisphere of young patients (frontal and temporal lobes were common), and epilepsy was one of the most common clinical symptoms 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the risk of seizures decreases with age and men were at higher risk than women. Tumor location (frontal, temporal, cap, pillow, island) and the WHO classi cation ( ~ grade) were also associated with BTRE [20][21] . The incidence of BTREs in frontal lobe, temporal lobe, insular lobe and parietal lobe were higher than that in deep tumor tissues 22 .…”
Section: Introductionmentioning
confidence: 96%
“…Закономерным результатом этих представлений стал выход новой классификации опухолей ЦНС ВОЗ от 2016 г. Впервые в основу классификации положено не только гистологическое строение новообразования, но и его наиболее значимая молекулярно-генетическая характеристика или хромосомная аберрация [77][78][79]. За последние годы в опухолях головного мозга было выявлено несколько молекулярных маркеров: мутации в гене изоцитратдегидрогеназы 1/2 (IDH1/2), коделеции 1p/19q, метилирование промотора MGMT, мутация К27М в гене H3F3A, мутация BRAF V600E и др., которые имеют существенное значение для прогноза и терапии заболевания [80][81][82][83]. В частности, F. Stockhammer et al обнаружили связь между эпиприступами, как первым симптомом опухоли, и наличием мутации IDH1/2 в диффузных глиомах низкой степени злокачественности [84].…”
Section: иммунологический статус и локальные иммунные реакцииunclassified
“…Differential diagnoses include astroblastoma, ependymoma, and papillary glioneuronal tumors. 21 Tumor cells do not harbor IDH or BRAF mutations, and the presence of either would suggest an alternative diagnosis. There is one report of malignant transformation to anaplastic ependymoma.…”
Section: Neuro-oncologymentioning
confidence: 99%